Penerapan Teknik Cognitive Restructuring Dalam Mengatasi Konsep Diri Yang Negatif Pada Waria (Studi Kasus Pada Klien “I” Di Muara Pinang Baru Kec. Muara Pinang Kab. Empat Lawang) - Peri Winata; Suryati suryati; Hartika Utami Fitri (ScidacPlus, 2023)
ABSTRACT: Deviant sexual behavior has been known since ancient times. The Koran mentions sexual deviations committed by his people, one of Prophet Luth was transvestites. The term transvestites is given to people who were born male, but have sexual and psychological tendencies as women. Transvestites are men who have characteristics, attitudes like women, look like women so that their daily lives are like women, but sometimes their male characteristics come out when things are tight. The purpose of this research is to determine the description of the self-concept and daily behavior of client